ROSE TINGED MEMORIES: A FAMILY OF STRANGERS (The Pretoria Student Law Review, 2021)
I took a drive to that dusty street whose length had once been filled with many families. To own the truth, I was led there by a longing to eat freshly baked cake in maTema’s kitchen with the banana tree that blocked the light from the window and feel her motherly gaze from behind her sixties styled pink sunglasses.
Keywords: memories; family; old friends